CROSS-COMMUNICATION AND ACT OF LISTENING: WOMEN MAKE HOUSEHOLD DECISIONS AS SELF-AUTONOMISING AGENCY - Puji Efriany Zain; Selti, Reynhard Malau, Elvita Erika, Rina Elisabeth, Gunawan Kristian, Andani Nainggolan (Adisam Publisher, 2023)
The background of this research is to uncover the atmosphere, events and test the stigma that decision makers are men in a family building or institution. The three research subjects in Central Kalimantan wanted to convey that decision makers are often women. This phenomenon is essential and makes a difference between the results of previous research or the existence of a stigma that women's voices are often drowned out when decisions are made in family institutions. This research is a qualitative research with data search through interviews with 3 research subjects who are in Central Kalimantan as well as those from outside Central Kalimantan (Bandung and West Kalimantan). The research data search was conducted by recording, transcribing, and transferring important and relevant transcripts to the discussion results section. The results of this study indicate that consistently with the narratives raised by the three narrators or research subjects, Ykchomhhkahna, Dhckbokra and Mkhcelmatiys, the author found that the decision maker in the family is still dominated by the wife, especially in decision making related to children's needs and household needs. This is particularly pertinent as in some cases men are the decision-makers.